P013 A single cell approach reveals immune cell dynamics in Inflammatory Bowel Disease (IBD) and highlights association of CD8 intraepithelial lymphocytes (IELs) with response to vedolizumab treatment. (21st January 2022) - Paraskevopoulou, M; Mayer, L; Krueger, A; Pattekar, A; Ramos, A; Fulton, M; Wai Lau, C; Chau, L; Ren, Y; Tondon, R; Al Garawi, A; Bittinger, K; et al.
Abstract: Background: Dysregulated immunity in the gut is central to the pathogenesis of inflammatory bowel disease (IBD) and its contribution to patient responses following biologic treatment is poorly understood. Single cell protein- and sequencing-based analyses have provided unprecedented understanding of cell heterogeneity and function in IBD. In this study, recent cytometry by time of flight (CyTOF) and single cell transcriptomics technology advancements have been leveraged to characterize the intestinal mucosa of IBD patients treated with vedolizumab. Methods: Single cell RNA sequencing from IBD mucosa biopsies were analysed to derive cell molecular signatures and deconvolute bulk transcriptomic datasets of UC patients treated with biologics. Cellular abundance differences in response to therapy were in-silico validated in both vedolizumab and anti-TNF treated patients. CyTOF analysis of intestinal biopsies from 24 UC patients and 29 healthy controls (HC) was applied to complement transcriptomic findings and further understand T cell dysregulation in disease activity and treatment response. CyTOF panels were focused on T cell polarization, memory differentiation, effector function and homing. Mucosal microbiota analysis by 16S rRNA gene sequencing was employed and correlated with patient/host cellular dynamics. Results: Deconvolution analysis of UC bulk transcriptomic data with single cell molecular signatures from mucosa biopsied samples (Smillie et al. ) revealed decreased abundance of CD8 IELs along with increased activated T cells, inflammatory/activated stromal cells in non-responders to both vedolizumab and anti-TNF therapy compared with responders and HC. CyTOF analysis of intestinal biopsies from patients responding or not responding to biologic treatment confirms cellular alterations at the protein level. Specifically, in patients that respond to vedolizumab, we observed greater levels of immune cells with CD8 IEL phenotype (CD8+ CD69+ CD103+) similar to HC. In contrast, in non-responder patients we observed lower levels of these cells but higher abundances of CD8+ Tc17 and CD4+ Th17 cells. In non-responders, Tregs were also elevated compared with responders and HC. Assessment of mucosal biopsies with 16S rRNA gene analysis also revealed microbial metabolic pathways supportive of CD8 IEL development associated with elevated CD8 IELs in vedolizumab treatment responders. Conclusion: This multi-modal and deep molecular phenotyping approach revealed CD8 IELs to be associated with healthy intestinal tissue and treatment response to vedolizumab. These findings suggest that CD8 IELs may be beneficial for supporting and restoring tissue homeostasis.